Implementasi Triple Modular Redundancy dengan Triplicated Voting pada Alat Pendeteksi Hujan - Lastio Irfathan Ananda; Mochamad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Fault tolerance is the ability of the system to be able to continue running even when it is damaged. Fault tolerance has several types that are often used, in this study will be discussed about TMR (Triple Modular Redundancy). TMR is a hardware redundancy technique that duplicates 3 computing modules, and there will also be a voter polling the computational module. The voter's job is to see if any of the computing modules are damaged. However, in this study, the TMR voter will also be triplicated to reduce the possibility of a single point of failure, namely the event that the system cannot function if one of the modules is damaged, in this case is the voter. The device used as a computing module in this study is Arduino Uno, this study also uses the FC-37 rain sensor as an experimental sensor to retrieve the data. The result of this research is that the reliability value of the Triple Modular Redundancy system with Triplicated Voting is 98.49%, which is an increase compared to Triple Modular Redundancy with only 1 voter, which is 92.74%. The success rate of experiments conducted on Triple Modular Redundancy with Triplicated Voting also generally increased.